Hypoglycemia Prevention Practice and Associated Factors among Diabetic Patients on Follow-Up at Public Hospitals of Central Zone, Tigray, Ethiopia, 2018 - Gebrewahd Bezabh Gebremichael; Teklewoini Mariye Zemicheal (International Journal of Endocrinology)
Background. Hypoglycemia is an acute medical situation that occurs when blood glucose level falls below 70 mg/dl. Although prevention of hypoglycemia is one cornerstone in the management of diabetes mellitus, its prevention practice among patients with diabetes mellitus is insufficiently studied. Moreover, the existed scarce literature in Ethiopia revealed hypoglycemia prevention practice is inadequate. Thus, this study tried to assess hypoglycemia prevention practices and associated factors among diabetic patients. Methods. Hospital-based cross-sectional study design was employed from March 1 to April 1, 2018, in the central zone of Tigray regional state of Ethiopia. A total of 272 diabetes mellitus patients selected by a systematic random sampling method were included in the study. Data were entered into Epi-data version 3.1 and exported to SPSS version 23 for further analysis. The binary logistic regression model (AOR, 95% CI, and p value < 0.05) was used to determine the predictors of hypoglycemia prevention practice. Results. The mean age of respondents was 43.62 years, and about 100 (63.2%) participants had good hypoglycemia prevention practice. Good knowledge on hypoglycemia (AOR = 10.34; 95% CI [5.41, 19.89]), having a glucometer at home (AOR = 3.02; 95% CI [1.12, 8.12]), favorable attitude towards diabetes mellitus (AOR = 2.36 CI [1.26, 4.39]), and being governmental employee (AOR = 5.19, 95% CI [1.63, 16.58]) were positive predictors of good hypoglycemia prevention practice. However, being divorced (AOR = 0.13, 95% CI [0.32, 0.53]) was found negatively associated with good hypoglycemia prevention practice. Conclusion. Only two-thirds of the study participants were found to have good hypoglycemia prevention practices. Healthcare personnel and Ethiopian diabetic association should promote patients’ attitude towards DM and knowledge on hypoglycemia by strengthening information, education, and communication program. Stakeholders should also try to provide glucometers to diabetic patients.